Development of new neuromodulation technologies as an alternative for improvement and insertion in the labor market (Research, Society and Development, 2022)
Introduction: Neuromodulation devices are already present in many patients' lives, like cardiac pacemaker, spinal cord stimulator for chronic pain treatment, cochlear implant, and even brain stimulation devices used for enhancing performance of athletes, gamers and students. It’s getting even harder to maintain neuromodulation research with high scientific and qualified production in Brazil due to political and economical issues that end leading to student grant cuts. The global market for neurotechnology moves billions in a year, with a growth trend of approximately US$13.3 billion by 2022. This literature review seeks to identify in the Neuromodulation Industry, an opportunity for professional performance, as a self-financing option and as a working field for neuroengineering and neurosciences students. For this, 44 references in English and Portuguese were selected, mainly dating from 2010 to 2020. Research in neurotechnology tends to increase after the creation in 2012, of the Human Brain Project. Neurological disorders affect a large portion of the global population, with a tendency to increase in the next few years, turning this into a profitable market with good future directions. The research into the field of neuromodulation is a marketable product and there are big companies in the business market that are interested in financing the development of new products and technologies, providing opportunities to neuroengineering and neurosciences students entering the formal labor market even before completing a graduate course.